Exploring dynamic change in arterial base excess with patient outcome and lactate clearance in the intensive care unit by hierarchical time-series clustering - Li, Dongkai; Liu, Shengjun; Zhang, Jiahui; Cheng, Wei; Mao, Jiayu; Cui, Na (Frontiers in Medicine, 2022)
Background: Hyperlactatemia is common in the intensive care unit (ICU) and relevant to prognosis, while the process of lactate normalization requires a relative long period. We hypothesized that the dynamic change in base excess (BE) would correlate be associated with ICU mortality and lactate clearance. Methods: We performed a retrospective cohort study of adult patients with hyperlactatemia admitted to the ICU from 2016 to 2021. The patients were divided into two groups according to whether the peak BE in 12 hours was reached in the first 6 hours. We compared ICU mortality and lactate clearance at 6 and 12 hours after ICU admission. Results: During the study period, 1,608 patients were admitted to the ICU with a lactate concentration of >2.0 mmol/L and stayed in the ICU for >24 hours. The mortality rate was 11.2%. The patients were divided into two groups according to whether the peak BE was reached in the first 6 hours following ICU admission: Peak BE12h≤6h and Peak BE12h>6h. The patients were also recorded as whether bicarbonate treatment was received (bicarbonate group, CRRT included) or not (non-bicarbonate group). Furthermore, lactic acid clearance patterns were identified by time-series clustering (TSC) using various algorithms and distance measures. We compared ICU mortality and lactate clearance at 6 and 12 hours after ICU admission with logistic regression. After adjustment for other confounding factors, we found that Peak BE12h>6h was independently correlated associated with ICU mortality with an odds ratio of 2.231 (p = 0.036) in the bicarbonate group and 2.359 (p < 0.005) in the non-bicarbonate group. Additionally, based on the definition of >10% lactate clearance at 6 hours or >30% at 12 hours, we found that Peak BE12h≤6h had 85.2% sensitivity and 38.1% specificity for effective lactate clearance. In time-series clustering analysis, four categories were discriminated, and pattern of lactic acid clearance reveal the early prognostic value of BE in clearance of lactic acid. Conclusions: A prolonged time to reaching the peak BE was independently associated with ICU mortality. In patients with hyperlactatemia, Peak BE12h≤6h could be used as an indicator to predict effective lactate clearance.